Antidepressants and the Suicide Rate: Is There Really a Connection? - Matz Dahlberg; Douglas Lundin (Uppsala University, Department of Economics, 2005)
Recent research claims that the major part of the observed reduction in suicide rates during the 1990s can be explained by the increase in the prescription of antidepressants. This conclusion is however based on research that only looks at raw correlations; confounding effects from other variables are not controlled for. Using a rich data set, we reinvestigate the issue. After controlling for other covariates, observed as well as unobserved, that might affect the suicide rate, we find, overall, no statistically significant effects from antidepressants on the suicide rate; when we do get significant effects, they are positive for young persons. Regarding the latter result, more research is needed before any firm policy conclusion can be made.
urn:nbn:se:uu:diva-211060
Keywords: C23; I12; 330; Suicide; antidepressants; Poisson fixed effects; Pharmazeutisches Produkt; Selbstmord; Schätzung; Schweden